2003
DOI: 10.1152/ajpheart.00317.2002
|View full text |Cite
|
Sign up to set email alerts
|

ANG II AT2receptor modulates AT1receptor-mediated descending vasa recta endothelial Ca2+signaling

Abstract: kidney; vasoconstriction; vasodilation; medulla; blood flow BLOOD FLOW TO THE MEDULLA of the kidney is maintained through the tonic and stimulated release of nitric oxide (NO). Intrarenal infusion of vasoconstrictors such as norepinephrine and angiotensin II (ANG II) cause vasoconstriction and a reduction of renal blood flow. In response to vasoconstrictor infusions, compensatory release of NO helps to preserve the small fraction of the total renal blood flow that reaches the medulla of the kidney (38,43,44). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…In that preparation, AT2R activation increases NO bioavailability by inhibiting generation of reactive oxygen species. 17,19 Taken together, the finding by Gonzales et al 1 that AT2R activation is vasodilatory largely supports previous observations.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…In that preparation, AT2R activation increases NO bioavailability by inhibiting generation of reactive oxygen species. 17,19 Taken together, the finding by Gonzales et al 1 that AT2R activation is vasodilatory largely supports previous observations.…”
supporting
confidence: 84%
“…Systemic AT2R activation through infusion of angiotensin II plus AT1 receptor blockers lowers blood pressure 9 and AT2-null mice have mild hypertension with an exaggerated blood pressure response to deoxycorticosterone acetate plus salt. 10,11 Carotid arteries, 12 coronary arterioles, 13 renal afferent arterioles, 14 -16 and descending vasa recta 17 are dilated by AT2R activation. The participation of bradykinin B2 receptor activation and NO generation in AT2R-mediated vasodilation is a common finding but it is not uniform in all experimental preparations.…”
mentioning
confidence: 99%
“…38 Our data regarding the effects of PD123319 therefore suggest that AT 2 receptor activation can blunt AT 1 -mediated release of vasodilator factors that act on vascular elements controlling MBF. At face value, this conclusion seems at odds with recent in vitro findings by Rhinehart et al 19 in isolated, outer medullary, descending vasa recta, vascular elements that are probably important in the control of MBF. They showed that AT 2 receptor activation blunted vasoconstrictor responses to angiotensin II in these vessels and also opposed angiotensin …”
Section: Discussionmentioning
confidence: 69%
“…Consistent with this notion, AT 2 receptor activation opposes AT 1 -mediated vasoconstriction and endothelial calcium signaling in isolated, descending vasa recta in vitro. 19 Therefore, we tested the effects of candesartan and PD123319 on the responses of regional kidney perfusion and renal excretory function to the renal-arterial administration (infusion and bolus) of angiotensin peptides in anesthetized rabbits. We tested the responses to angiotensin II itself, angiotensin III (moderate selectivity for AT 2 receptors 20,21 ), the highly selective AT 2 agonist CGP42112A, 22 and angiotensin(1-7), because the latter has both a high affinity for AT 2 receptors 21 and vasodilator effects that are possibly mediated independently of AT 1 and AT 2 receptors.…”
mentioning
confidence: 99%
“…AT2R-dependent activation of phosphatases could modulate the phosphorylation of contractile proteins and their sensitivity to increases in [Ca 2ϩ ]i, leading to vasodilation without a marked reduction of intracellular calcium. 45,46 However, considering the technical limitations of the present study, this and other potential mechanisms implicated 6 will need further investigation.…”
Section: Discussionmentioning
confidence: 86%